Total secondary metabolites and heavy metal profile of some medicinal plants frequently consumed as winter tea - Karagozoglu, Yusuf; Alayunt, Naci Ömer; Parlak, Akıf Evren (My University, 2023)
In this study, sage (Salvia officinalis L.), linden (Tilia platyphyllos Scop.), and daisy (Matricaria chamomilla L.) herbs, which have rich phytochemical content and are frequently consumed in winter months for medicinal purposes, were obtained from three different herbalists located in Bingol and investigated in terms of their heavy metal contents, total flavonoid, total anthocyanin and total polyphenol contents. Some of the heavy metal (Cr, Fe, Co, Ni, Cu, Zn, As, Hg, Pb) contents of the collected herb samples were determined by ICP-MS. Total flavonoid, total anthocyanin and total polyphenol contents were determined by analyzing spectrophotometric methods. While the total phenolic content was found the most in sage (S1) ethylacetate and methanol extracts (760.1±2.0, 410.33±1.5 mg GAE/g), it was found the least in linden (L1, L3) hexane extracts (6.66±.1.3, 8.35±0.8 mg GAE/g). It was determined that total flavonoid content and total anthocyanin contents were higher in sage (S1) ethylacetate (294.31±2.1 mg CE/g and 291.31±2.1 mg MvGE/g), sage (S2) methanol (375.0±1.9 mg CE/g and 139.01*±2.0 mg MvGE/g) extracts, and less in linden (L1) and daisy (D1) hexane extracts respectively. It was determined that Cr and Cu metals were among the values suitable for consumption in terms of health in all samples except the chamomile (D1, D3) samples, and Zn metals were among the values suitable for consumption in all samples except the linden (L2) sample. Furthermore, the toxic metal Cd (0.05±0.00- 0.09±0.00 ?g/g) in daisy (D1, D3) samples, as well as the other toxic metal Pb (4.50±0.01-6.43±0.01 ?g/g) in sage (S1,S2,S3) and linden (L1,L2,L3) samples, were found to be among the values suitable for consumption in terms of health. As a result, when the total anthocyanin, polyphenol and flavonoid contents were compared in all groups it was found that sage had the highest value in ethyl acetate extract. Additionally, Cu and Ni values of sage, and Fe and Pb values in both sage and linden were within safe limits in terms of health. They are of utmost importance in terms of supporting the daily mineral intake. However, As, Pb, and Hg were found to be toxic in daisy extract. This result can be shown as a result that the daisy will be a bioaccumulator. Therefore, consumption of daisy tea should be limited.
Keywords: Total flavonoid; Heavy metal; Sage; Linden; Herbal Tea; Daisy; Total anthocyanin; Total polyphenol